Preparation of Porphyrin/ZnO Organic-Inorganic Hybrid and Its Hydrogen Sensing Property at Low Temperature - Dang, Thi Thanh Le; Tonezzer, Matteo; Nguyen, Thi Bac; Nguyen, Van Hieu (Old Journal, 2017)
Gas sensor based on a microbelt of ZnO coated the fluorinated tetraphenylporphyrin (H2TPPF) layer structured islands were developed for detection of H2 at low temperature. ZnO single microbelt was synthesized by thermal evaporation at 500-600°C, which was used to coat H2TPPF directly via supersonic molecular beam deposition (SuMBD) on the surface of ZnO microbelt for the gas sensor application. The morphology of the ZnO microbelt sensor was examined by field-emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). The diameter and length of the microbelt were 5 µm and 220 µm, respectively. The porphyrin islands height was few tens of nanometers. The fabricated sensor showed a good response to hydrogen at quite low working temperature. The mechanism of the hybrid sensor needs to be studied further in future.